2020
DOI: 10.1096/fj.202000391rr
|View full text |Cite
|
Sign up to set email alerts
|

GPA peptide enhances Nur77 expression in intestinal epithelial cells to exert a protective effect against DSS‐induced colitis

Abstract: Ulcerative colitis (UC), an intractable inflammatory bowel disease (IBD), is a chronic and idiopathic inflammatory disease which affects the colon, resulting in weight loss, diarrhea, rectal bleeding, and abdominal pain. 1-4 In the inflamed tissue of patients with UC, the tight junctions of epithelium are disrupted, enabling microbes to migrate from the lumen into the lamina propria. Once the NF-κB pathway is activated, large amounts of pro-inflammatory cytokines will be produced to cause a cycle of uncontroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…After histological examination, the histopathology grading scores for colonic sections were measured as previously described with slight modifications. 21…”
Section: Histological Analysesmentioning
confidence: 99%
“…After histological examination, the histopathology grading scores for colonic sections were measured as previously described with slight modifications. 21…”
Section: Histological Analysesmentioning
confidence: 99%
“…GPA peptide was procured from Top Peptide Biotechnology Co., Ltd. (Shanghai, China). The dosage of GPA peptide was chosen based on prior studies [ 9 , 13 ]. Administration of GPA peptide (50, 100, or 150 mg/kg) to the GPA peptide cohort and CLP+GPA peptide cohort was done via oral gavage at one dose each day for 7 days prior to and during CLP treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Gly-Pro-Ala (GPA) peptide, extracted from gelatin hydrolysate of fish skin, has been proven to have antioxidant and anti-inflammatory effects either in vivo or in vitro [ 8 ]. Recent literature demonstrated that Nur77 mitochondrial translocation is induced by GPA peptide, which impedes inflammation and oxidative stress by promoting autophagy subsequently [ 9 ]. Moreover, GPA peptide was also discovered as a potential therapy in DSS-induced colitis through blocking ROS and mtDNA production along with inhibiting pyroptosis in macrophages and the activation of NLRP3 inflammasome [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic and intractable digestive tract inflammatory disease that affects the millions of people; blocking immune responses and inflammatory cytokines have become effective strategies for treating colitis. NR4A1 (also known as TR3, NGFIB or Nur77), a member of the nuclear receptor NR4A family, exerts a protective role in colitis, 1 , 2 however, its effect and mechanism on pyroptosis or NLRP3 inflammasome is still unclear.…”
Section: Figurementioning
confidence: 99%